Graphene-Based Ammonia Sensors Functionalised with Sub-Monolayer V2O5: A Comparative Study of Chemical Vapour Deposited and Epitaxial Graphene † - Margus Kodu; Artjom Berholts; Tauno Kahro; Jens Eriksson; Rositsa Yakimova; Tea Avarmaa; Indrek Renge; Harry Alles; Raivo Jaaniso (Sensors, 2019)
Graphene in its pristine form has demonstrated a gas detection ability in an inert carrier gas. For practical use in ambient atmosphere, its sensor properties should be enhanced with functionalisation by defects and dopants, or by decoration with nanophases of metals or/and metal oxides. Excellent sensor behaviour was found for two types of single layer graphenes: grown by chemical vapour deposition (CVD) and transferred onto oxidized silicon (Si/SiO2/CVDG), and the epitaxial graphene grown on SiC (SiC/EG). Both graphene samples were functionalised using a pulsed laser deposited (PLD) thin V2O5 layer of average thickness ≈ 0.6 nm. According to the Raman spectra, the SiC/EG has a remarkable resistance against structural damage under the laser deposition conditions. By contrast, the PLD process readily induces defects in CVD graphene. Both sensors showed remarkable and selective sensing of NH3 gas in terms of response amplitude and speed, as well as recovery rate. SiC/EG showed a response that was an order of magnitude larger as compared to similarly functionalised CVDG sensor (295% vs. 31% for 100 ppm NH3). The adsorption site properties are assigned to deposited V2O5 nanophase, being similar for both sensors, rather than (defect) graphene itself. The substantially larger response of SiC/EG sensor is probably the result of the smaller initial free charge carrier doping in EG.